PHILOSOPHICAL CHARACTERISTICS OF SPORT IN THE FORMATION OF PERSONAL MORALITY (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the socio-philosophical features of sports in the formation of individual morality. It examines sport not only as a physical activity but also as an important social institution that shapes ethical values such as discipline, responsibility, perseverance, justice, and respect for others. The study highlights that in contemporary society, sport plays a significant role in moral education by influencing personal worldview, behavioral standards, and social adaptation processes. From a socio-philosophical perspective, sport is interpreted as a cultural phenomenon that integrates ethical norms into human consciousness through competition, cooperation, and self-development. The article also explores how sporting practices contribute to the internalization of moral principles and the strengthening of social solidarity. Special attention is given to the role of sport in youth moral upbringing and the development of socially responsible personality traits in the context of globalization.
Keywords: Sport, morality, ethics, socio-philosophy, personality development, socialization, moral education, youth, cultural values, social solidarity.